The school organization and the limits of the mediation of the inspectors in the Secondary Schools - Ángel Lorente Lorente (ADIDE Federación, 2006)
One of the inspection functions best valued by the school management teams is the one devoted to the mediation and arbitration, closely related to the function of expert advice, especially when a conflict arises among teaching staff. And now a reflection on the organisation bases of the school institution is proposed, where these conflicts come up and develop, like keys we cannot do without, due to its structural scope in the entire educational establishment. We are going to talk about the culture, the relationships and the structures just like constituent dimensions of the whole school organisation. So, reflecting on the specific professional culture of the Secondary teachers or on the nature of the micropolitical relationships that take place in High Schools will help us to understand the possibilities and limits of our function of mediation and expert advice in order to be able to contribute, in situations like that, to the improvement of the educational establishments.